Possible contamination points of lubricating oil by silica in diesel engines (Research, Society and Development, 2020)
The high cost of maintenance and expenses with lubricants are cited as disadvantages of agricultural mechanization. The fleet maintenance sector is responsible for a large part of the costs in agro-industrial properties and any innovation employed to reduce these costs can directly impact the final price of the product. A laboratory analysis of lubricating oil is one of the main maintenance tools for checking for abnormalities in the diesel engine and makes it possible to monitor physical and physical conditions through analyzes that point out the presence of contamination by water, ferrous particles and external contaminants such as Silica, which may come from dust, is one of the main sources of contamination of lubricating oil, being the most common cause of wear. Given the context, the objective of this article is to indicate the possible points of contamination of the lubricating oil of the diesel engine by Silica and to propose a check list that can be used in a detailed visual precision, to be inserted in the preventive maintenance routine of agricultural tractors, with the identification of identification of possible contamination by external elements, thus preventing the system from continuing to be contaminated until the results of laboratory analysis arrive.